The stressed state of the Earth’s crust in the Altai-Sayan mountain region: reconstruction based on the modified algorithms of the cataclastic method - @Rebetsky, Yuri L.; Sycheva, Naylya A. (Геосистемы переходных зон)
The article presents the results of a new reconstruction of stress in the Earth’s crust in the Altai-Sayan mountain region and their adjacent territories based on seismological data, and using a new modification of the method of cataclastic analysis (MCA) of fault displacements by Yu.L. Rebetsky. The reconstruction is based on the catalog of earthquake focal mechanisms collected from various sources and comprising 584 events. In earlier works by Yu.L. Rebetsky et al. (2012, 2013), the data on focal mechanisms of 308 events obtained in the studies of N.D. Zhalkovsky et al. (1995) were used for studying the Altai-Sayan mountain region. This paper discusses the modified algorithms implemented in the latest version of the STRESSseism program, on the basis of which the stress reconstruction was performed. The extended data on focal mechanisms provided the stress inversion with a smaller averaging scale and allowed obtaining data for a larger number of time intervals of the quasi-homogeneous stress state in each node. Distribution maps of the directions of the maximum compression axis and the geodynamic type of the stress state, as well as the value of the Lode – Nadai coefficient were constructed and compared with the results of the previously performed reconstruction. Based on the modification of the MCA algorithm, stable orientations of the axes of the principal stresses were obtained. The results of the stress reconstruction can be used for tectonophysical zoning of dangerous segments of active faults.